2008
DOI: 10.1038/onc.2008.289
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of telomeres in human cancer

Abstract: Hypomethylation of repeated elements in the genome is a common feature of human cancer, however, the direct consequences of this epigenetic defect for cancer biology are still largely unknown. Telomeres are specialized chromatin structures at the ends of eukaryotic chromosomes formed by tandem repeats of G-rich sequences and associated proteins, which have an essential role in chromosome end protection and genomic stability. Telomeric DNA repeats cannot be methylated, however, the adjacent subtelomeric DNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 30 publications
8
90
3
Order By: Relevance
“…This is evidenced by the low methylation level of pericentromeric Sat2 DNA and Alu repeats, two markers of genome-wide demethylation in tumors (Weisenberger et al, 2005;Cadieux et al, 2006;Ehrlich, 2006), in ALT tumor cell lines. It is worth noting that when this article was in preparation, a study on epigenetic regulation of human telomeres reported no correlation between the methylation level of subtelomeric DNA and the pericentromeric repeat NBL2 DNA (Vera et al, 2008). We believe that the discrepancy between this study and the present one may be related to the fact that NBL2-repeated sequences are known to undergo opposite cancer-linked epigenetic changes, displaying either hypomethylation or, more frequently, predominant hypermethylation in tumors (Ehrlich, 2006).…”
Section: Discussioncontrasting
confidence: 81%
“…This is evidenced by the low methylation level of pericentromeric Sat2 DNA and Alu repeats, two markers of genome-wide demethylation in tumors (Weisenberger et al, 2005;Cadieux et al, 2006;Ehrlich, 2006), in ALT tumor cell lines. It is worth noting that when this article was in preparation, a study on epigenetic regulation of human telomeres reported no correlation between the methylation level of subtelomeric DNA and the pericentromeric repeat NBL2 DNA (Vera et al, 2008). We believe that the discrepancy between this study and the present one may be related to the fact that NBL2-repeated sequences are known to undergo opposite cancer-linked epigenetic changes, displaying either hypomethylation or, more frequently, predominant hypermethylation in tumors (Ehrlich, 2006).…”
Section: Discussioncontrasting
confidence: 81%
“…32 In these studies, the methylation frequency was evaluated by BGS at two subtelomeric sites, and DNA methylation of subtelomeric D4Z4 repeats on chromosome 4q showed a significant negative correlation with telomere length (p < 0.01), while the other site, an independent subtelomeric repeat, SRH, located on chromosomes 1, 9, 15, 16 and X, showed a marginally significant negative correlation (p ¼ 0.07). 32 In our study, correlations between telomere length and methylation ratio were found in certain regions of subtelomeres. Methylation at 7q gradually decreased with telomere lengthening of HCCs, and a similar relationship was found at 18p in both HCCs and non-HCCs, indicating that hypomethylation in these regions might be related to long telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the researchers focused on the putative effects of the epigenetic changes in cancer for development of early diagnosis methods and new therapeutic approaches (25,26). This new perspective was proven by Vera et al They found an association between DNA methylation of global/ subtelomeric region and telomere-SCE frequency (27).…”
Section: Figure 1 Sce Distribution Of Measurements According To Groupsmentioning
confidence: 96%